2018
DOI: 10.1590/1809-4392201800382
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the micropropagation potential of curauá pineapple hybrids for fiber production

Abstract: Plant fiber is a renewable and biodegradable material that can be used effectively to reinforce various composites. Pineapple hybrids selected for their fiber quality are in the phase of agronomic validation in Brazil by the Embrapa Cassava and Fruits research unit. The selection of a hybrid for large-scale fiber production depends on obtaining a large number of seedlings. This study evaluated the morphogenetic response and propagation potential of eight hybrids of Ananas comosus var. erectifolius, for the pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
1
1
Order By: Relevance
“…The geometric growth rates found in this study show an atypical behavior of what has been shown in other studies, such as Silva et al (2016) and Souza et al, (2018), which observed a decrease in propagation potential in pineapple after the third subculture.…”
Section: Micropropagationcontrasting
confidence: 51%
“…The geometric growth rates found in this study show an atypical behavior of what has been shown in other studies, such as Silva et al (2016) and Souza et al, (2018), which observed a decrease in propagation potential in pineapple after the third subculture.…”
Section: Micropropagationcontrasting
confidence: 51%
“…The selection of the explant and the culture medium are basic conditions for establishing an in vitro propagation protocol or in vitro conservation method (JIANG et al, 2012). The cultivation medium, MS (MURASHIGE &SKOOG, 1962), has proven to be efficient and responsive in most herbaceous species such as banana, pineapple, and strawberry (GALAN et al, 2018;SOUZA et al, 2018;MOZAFARI et al, 2018). However, woody species have other needs, especially for basic salts.…”
Section: Introductionmentioning
confidence: 99%